Nurses’ Experience of Using an Application to Support New Parents after Early Discharge: An Intervention Study - Dorthe Boe Danbjørg; Lis Wagner; Bjarne Rønde Kristensen; Jane Clemensen (International Journal of Telemedicine and Applications)
Background. A development towards earlier postnatal discharge presents a challenge to find new ways to provide information and support to families. A possibility is the use of telemedicine. Objective. To explore how using an app in nursing practice affects the nurses’ ability to offer support and information to postnatal mothers who are discharged early and their families. Design. Participatory design. An app with a chat, a knowledgebase, and automated messages was tried out between hospital and parents at home. Settings. The intervention took place on a postnatal ward with approximately 1,000 births a year. Participants. At the onset of the intervention, 17 nurses, all women, were working on the ward. At the end of the intervention, 16 nurses were employed, all women. Methods. Participant observation and two focus group interviews. The data analysis was inspired by systematic text condensation. Results. The nurses on the postnatal ward consider that the use of the app gives families easier access to timely information and support. Conclusions. The app gives the nurses the possibility to offer support and information to the parents being early discharged. The app is experienced as a lifeline that connects the homes of the new parents with the hospital.